STUDY OF THE SAFINATUN NAJAH BOOK AS A RELIGIOUS LITERACY STRENGTHENER FOR STUDENTS AT MI AL MA’HAD AN NUR BANTUL - Koyim, Muh; Samsudin; Ichsan, Ahmad Shofiyuddin (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
To improve religious literacy in students, the academic community of Madrasah Ibitidaiyah (MI) applies Madrasah Diniyah learning with the study of the Safinatun Najah book. The purpose of this research is to determine the importance of the study of the Safinatun Najah book in Madrasah Ibtidaiyah Al Ma'had An Nur Bantul and how the process of implementing the study of the book is used as a strength of religious literacy for students at MI Al Ma'had An Nur Bantul. The researchers used qualitative research with a case study type—data collection techniques used through observation, interviews, and documentation. The research results reveal that the study of the Safinatun Najah book was carried out in the form of nadham written in Arabic Pegon in Indonesian. This research is used to teach Fiqh related to Ubudiyah in a concise but comprehensive manner. This research can help students understand and carry out worship correctly and maintain cleanliness and purity. Not only that, this research is able to help strengthen not only religious literacy but Arabic reading literacy. By utilizing the nadham method, students are more interested, making it easier to improve memorization. The learning process includes the teacher reading the nadham and explaining the material, students imitating and discussing it, and students practicing the material in everyday life.